TOWARDS IMPROVING SERVICE DELIVERY AND THE QUALITY OF LIFE FOR THE MARGINALISED GROUPS IN NIGERIA - Ipadeola, Mairo Hamid; Atteng, Catherine James (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2021)
There is a steady increase in the number of children with special needs and disadvantage groups due poverty, conflicts, disasters, disease and accidents. While service delivery to these group has be characterized by humanitarian approach, the Nigeria government is ascending towards the compliance approach which necessitates legislations, in 2019 the bill protecting the rights of people with disabilities was passed into law. However, the most appropriate approval recommended is the citizenship approach which implies that the people with disabilities are regarded as equal citizens with full rights and responsibilities, economically, politically and morally. Clearly spelt out in the National Policy on Education (NPC) 2014, Education is the right of every individual in Nigerian to Education and the development of individuals into a sound and effective citizen and the provision of equal opportunities for all citizens. The NPC further states in section 7 the provision for special Education. These laudable policy is achieve to certain extent due to barriers such as attitudinal, physical and environmental, systematic, economic and employment facing majority of children with special needs or disadvantage children in accessing both public and private services. Some recommendations for the way forward include, changing disability image and reduce negative attitude toward people with disabilities. Documentation of all categories of people with disabilities in the state for purpose of planning and funding for special Education. Planning for increase enrolment of children with special needs in both public primary, secondary and higher institutions in the state. Restructuring of the regular curriculum, placement of pupils and personnel’s. Restructuring of curriculum, placement of pupils and personnel’s in both regular and special primary / secondary schools in Nigeria. Improving physical and environmental barriers. Provision of legislation to protect the rights of people with disabilities. Increase number of people with disabilities in the work force and fixed at- least 2% of the total budget for special education. As stakeholder we have moral obligations to extend equity in service delivery to children and adults with special needs.